The Role of Counselor in Developing Student's Assertive Behavior - Annisa Arrumaisyah Daulay; Daharnis Daharnis; Afdal Afdal (International Conferences on Educational, Social Sciences and Technology)
Assertive behavior has an important role for students as a means of control in performing an action and the ability to express emotions appropriately. Students who are not assertive, indicated resources by reviews their dependence on the environment, lack of understanding of reviews their needs, and difficult, to say 'no', so easily affected and carriedaway in negative environments. Therefore, students need to be given understanding and training from professionals. One of the which is a counselor through guidance and counseling services to direct and help develop student assertive behavior in order to live a better life in the future. This paper discusses the basic concepts of assertive behavior and the role of counselors to assist students in developing assertive behaviors.